A Scalability Enhancement Scheme for Ethereum Blockchains: A Graph-based Decentralized Approach - Khan, Burhan Ul Islam; Goh, Khang Wen; Zuhairi, Megat F.; Putra, Rusnardi Rahmat; Khan, Abdul Raouf; Chaimanee, Mesith (Engineering, Technology & Applied Science Research, 2024)
Amidst the rising demands for data security across expansive networks, blockchain technology is witnessing an upsurge in its adoption, particularly within Internet of Things (IoT) applications, services, and smart cities. Blockchains offer an immutable property that bolsters security and aids in the structured management of distributed ledgers. Nevertheless, ensuring scalability remains a formidable challenge, especially within decentralized Ethereum systems. Current methods often fall short of offering tangible solutions, and the scrutiny of Ethereum-based cases reveals persistent deficiencies in addressing scalability issues due to inherent system complexities, dependency on resource-intensive consensus algorithms, lack of optimized storage solutions, and challenges in ensuring synchronous transaction validation across a decentralized network. This paper proposes a foundational scheme underpinned by a unique graph-based topology and hash bindings for nodes that join the system. The proposed scheme establishes an innovative indexing mechanism for all transactions and blocks within the IoT framework, ensuring optimal node accessibility. Transaction and block replications occur over the joining nodes' graphical structure, ensuring efficient subsequent retrieval. A standout feature of the proposed scheme is its ability to enable participating nodes to forgo retaining a complete ledger, making it non-reliant on individual node capabilities. Consequently, this facilitates a broader spectrum of nodes to participate in the consensus system, irrespective of their operational prowess. This study also offers a novel empirical model for Proof-of-Validation (PoV), which reduces computational intricacy and expedites the validation process in stark contrast to prevailing blockchain systems.